A specific, rapid and high-throughput cascade catalytic method for determination of plasma uric acid by using uricase and trivalent peroxidase-mimicking DNAzyme. (March 2020) - Karami, Zahra; Sohrabi, Nasrin; Badoei-dalfard, Arastoo
Abstract: In this study, we report a facile and cost-effective system for selective measurement of uric acid (UA) using a cascade mechanism composed of Uricase and peroxidase-mimicking trivalent DNAzyme. A three G-quadruplex-hemin complex was engaged as the peroxidase-mimicking DNAzyme. In this cascade catalysis system, UA was oxidized by uricase to produce hydrogen peroxide, which was also acted as a substrate for the oxidation of 3, 3′, 5, 5′ tetramethylbenzidine (TMB) by a peroxidase-mimicking trivalent DNAzyme. TMB oxidation showed a straight relationship with UA concentration. The cascade catalysis system displayed high selectivity toward UA because of the natural selectivity of uricase. This cascade uric acid sensing system revealed the best activity at 30 °C and pH 7.0, which indicated its capacity to uric acid sensing near physiological conditions. The linear regression equation for UA was quantified as A = 0.0072C + 0.0197, with a correlation coefficient of 0.9906. Results suggested that this system could identify as low as 0.66 μM of uric acid with a linear range from 2.5 to 40 μM. Results exhibited that the interfering public components had no noticeable absorbance values. Overall, these results indicated that this facile system would be valuable for uric acid measurement in the medical laboratory. Graphical abstract: Image 1 Highlights: The Uricase/peroxidase-mimicking Trivalent DNAzyme system presented high selectivity concerning uric acid. This cascade catalyst system showed the optimal activity near the physiologic condition. The linear range for uric acid sensing was from 2.5 to 40 μM. The LOD for uric acid sensing was measured as 0.66 μM. The recoveries for UA in urine samples were between 97.8% and 101.3%.